Enhancing Physics Learning in Sekolah Indonesia Kuala Lumpur (SIKL) by Utilizing Artificial Intelligence - Khalif, Muhammad Ardhi; Saputri, Affa Ardhi; Juwanda, Kuntoro Adi; Sudarmanto, Agus; Fatimatuzzahro, Voni (LP2M of Institute for Research and Community Services - UIN Walisongo, 2024)
The surge in digital learning technology, particularly Artificial Intelligence (AI), has reshaped education. This community service initiative at Sekolah Indonesia Kuala Lumpur in Malaysia targets AI training to innovate physics education. The multifaceted approach encompasses preparation, implementation, and evaluation stages, employing methods like Focus Group Discussions, training sessions, and mentoring. AI plays a pivotal role in assisting students with assignments, analyzing physics problems, and creating presentation media for school tasks, utilizing applications such as Canva+ChatGPT and Google Slides+ChatGPT. Training outcomes at Sekolah Indonesia Kuala Lumpur showcase participants' proficiency in AI-driven presentation media, achieving an impressive average score of 84.67. Among 27 participants, only one fell short of the 75-point passing criteria. To maximize AI's role in physics learning, ongoing implementation and support are crucial in subsequent activities.